Telepacífico labels project: ¿transmedia or non-transmedia? (2020)
This text aims to label LABELS as transmedia (or not), the first project of the Regional Channel called Telepacífico, with an LGBTI theme self-designated as transmedia. To do this, we will return to some approaches and principles around this adjective (or noun); and we will contrast them with the Labels proposal, in order not only to determine whether or not it is transmedia, but also to generate constructive contributions for future projects of this nature